Blended memory: A framework for understanding distributed autobiographical remembering with photography. (December 2020) - Fawns, Tim
This article offers a framework for understanding how different kinds of memory work together in interaction with people, photographs and other resources. Drawing on evidence from two qualitative studies of photography and memory, as well as literature from cognitive psychology, distributed cognition and media studies, I highlight complexities that have seldom been taken into account in cognitive psychology research. I then develop a 'blended memory' framework in which memory and photography can be interdependent, blending together as part of a wider activity of distributed remembering that is structured by interaction and phenomenology. In contrast to studies of cued recall, which commonly feature isolated categories or single instances of recall, this framework takes account of people's histories of photographic practices and beliefs to explain the long-term convergence of episodic, semantic and inferential memory. Finally, I discuss implications for understanding and designing future memory research.